2021
DOI: 10.1007/s10956-020-09886-w
|View full text |Cite|
|
Sign up to set email alerts
|

Biology Undergraduate Students’ Graphing Practice in Digital Versus Pen and Paper Graphing Environments

Abstract: Graphing is an important practice for scientists and in K-16 science curricula. Graphs can be constructed using an array of software packages as well as by hand, with pen-and-paper. However, we have an incomplete understanding of how students’ graphing practice vary by graphing environment; differences could affect how best to teach and assess graphing. Here we explore the role of two graphing environments in students’ graphing practice. We studied 43 undergraduate biology students’ graphing practice using eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Research that highlights some of the differences between environments when learning to work with data in pen-and-paper and digital modalities indicates that there are specific learning benefits and weaknesses of each environment (Gardner et al, 2021). Making the transition from working with small, self-collected datasets to larger datasets typical of what is collected at scale may be a valuable skill for learners (Kjelvik & Schultheis, 2019;Wolff et al, 2019).…”
Section: Digital Sources Of Data and Digital Tools For Analysing Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Research that highlights some of the differences between environments when learning to work with data in pen-and-paper and digital modalities indicates that there are specific learning benefits and weaknesses of each environment (Gardner et al, 2021). Making the transition from working with small, self-collected datasets to larger datasets typical of what is collected at scale may be a valuable skill for learners (Kjelvik & Schultheis, 2019;Wolff et al, 2019).…”
Section: Digital Sources Of Data and Digital Tools For Analysing Datamentioning
confidence: 99%
“…Yet, with datasets expanding in size and complexity, technology may become necessary to help students utilize these new types of data. The same practices done on paper can be performed using digital tools as well, however the learning opportunities using each modality may differ (Gardner et al, 2021; Kjelvik & Schultheis, 2019; Schultheis & Kjelvik, 2020). For example, a study on student graphing in paper and digital environments found that student graph quality was similar across platforms, however students found it easier to graph in digital environments and were better able to identify the appropriate variables for the graphs (Gardner et al, 2021).…”
Section: What Advances In Analysing Data Suggest For Science Teachers...mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, research showed the importance of including MR training in initial teacher education programs to support its use by PSTs in teaching science [32][33][34][35][36]. In one study [8], the participants were 15 preservice science teachers and they were enrolled in a course originally designed to allow PSTs to design and conduct open-ended experiments.…”
Section: Background 21 Multiple Representations In Physics Teachingmentioning
confidence: 99%